2023
DOI: 10.1161/jaha.122.027930
|View full text |Cite
|
Sign up to set email alerts
|

Third‐Trimester Maternal Serum Chemerin and Hypertension After Preeclampsia: A Prospective Cohort Study

Abstract: Background Limited data are available for postpartum hypertension prediction after preeclampsia. Methods and Results We examined the association between maternal serum chemerin levels in patients with preeclampsia and blood pressure (BP) levels after delivery in a prospective birth cohort of 15 041 singleton pregnant women. A total of 310 cases among 322 patients with preeclampsia (follow‐up rate, 96.3%) were followed up during a mean 2.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Several studies also reported a correlation of chemerin levels with the severity of PE [48,49,51]. A positive association between chemerin levels towards the end of pregnancy in PE patients and maternal hypertension after birth was also described by Chen et al, in a prospective cohort study [50].…”
Section: Chemerin In Gdm and Pementioning
confidence: 61%
See 1 more Smart Citation
“…Several studies also reported a correlation of chemerin levels with the severity of PE [48,49,51]. A positive association between chemerin levels towards the end of pregnancy in PE patients and maternal hypertension after birth was also described by Chen et al, in a prospective cohort study [50].…”
Section: Chemerin In Gdm and Pementioning
confidence: 61%
“…With regard to PE, reports were much more uniform. Two case-control studies, two cohort studies, one cross-sectional study, as well as one systemic review found chemerin levels in maternal serum to be significantly elevated in patients with PE [47][48][49][50][51][52]. Stepan et al, demonstrated that chemerin levels are not only increased during preeclamptic pregnancies but also remain elevated 6 months post-partum [47].…”
Section: Chemerin In Gdm and Pementioning
confidence: 99%
“…The incidence of postpartum hypertension in patients with PE was 45%, whereas in the control group, it was 17.4%. Maternal third-trimester chemerin serum levels positively correlated with postpartum blood pressure, and the authors concluded that chemerin may serve as a marker for the early prediction of postpartum hypertension [ 134 ]. Together with the results of another study confirming elevated chemerin serum levels 6 months after delivery in former PE patients in comparison to healthy controls [ 73 ], it is possible that chemerin might be one of the factors linking PE and future cardiovascular risk, but it needs further research.…”
Section: Important Implications Of Chemerin Involvement In Pe Pathoph...mentioning
confidence: 99%
“…Since the circulating concentrations of chemerin are positively correlated with insulin resistance, BMI, and serum triglycerides, it has been suggested that chemerin may play an important role in metabolic diseases; however, this is not yet conclusive [150]. Women with GDM or PE have higher chemerin levels than healthy pregnant women [151][152][153].…”
Section: Perspectives On the Study Of Adipokines In Excess-weight Pre...mentioning
confidence: 99%